Adverse Effect of Methane Gas on Environment and Its utilization for Economic Growth - GUPTA, ANUP KRISHNA; Dutta, Ajoy Kumar (IJRDO - Journal of Business Management, 2018)
Coal is a major source of energy. It has stimulated India's industrialization and is being used to produce thermal electricity (around 70%) and in the manufacturing industries like textile, steel, chemicals, fertilizers, etc. The increased trend of coal production conjoined with venting of methane into the atmosphere is causing a serious concern about the environmental pollution, in as much, the methane has a global warming potential, 21 times greater than carbon dioxide on a molecule by molecule basis and 58 time by mass.Indian coal seams has a vast Coal Bed Methane (CBM) potential in various coalfields.Methane is a potent green house gas emissions released into atmosphere by mining activities. Thus creating a hazardous situation for fragile atmosphere and 0zone layer.Methane is associated with coal as a by product in the coal formation process. It is trapped in coal beds and released during and after mining. This methane does cause disasters in underground coal nines. To reduce its hazards of emission and explosion, mines are ventilated with large quantities of air to reduce its percentage in mine air to a safe limit This diluted methane is released into the atmosphere and contributes to global climate change. Technologies are now available to recover the trapped methane from coal beds and thus provide an additional clean source of energy while reducing both escape of methane to the atmosphere and the mining hazard.